Comment on 'The central role of forests in the 2021 European floods'. (1st April 2023) - Staal, Arie; Koren, Gerbrand
Abstract: In July 2021, parts of Germany and Belgium were hit by severe floods. In 'The central role of forests in the 2021 European floods', published in Environmental Research Letters (2022 Environ. Res. Lett. 17 064053), Insua-Costa et al reported that 'moisture from North American forests was a more important source [of the rainfall contributing to the event] than evaporation over nearby seas'. This suggests that the event was (partly) caused by anomalous contributions from North America. In this comment, we show that this is a misleading interpretation, as: (1) the relative contribution of North American land was below average for the time of year; and (2) rather, the anomalous moisture that contributed to the floods originated mainly from European land. However, consistent with Insua-Costa et al, we find no enhanced evaporation from Europe prior to the event and we therefore conclude that there is a lack of evidence for the 'central role' of forests in the 2021 European floods.